2010
DOI: 10.1016/j.ijpsycho.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Rate of cardiovascular recovery to combined or separate orthostatic and mental challenges

Abstract: Post stress neurovascular responses induced by physical and mental stress are poorly understood. We investigated the time course of cardiovascular and autonomic recovery, induced by orthostatic and mental challenge, using passive head up tilt (HUT) and mental arithmetic (MA), respectively, when applied singly (MA, HUT) or in combination (MA + HUT). Fifteen healthy males participated in three protocols: HUT, MA and combined MA + HUT, with sessions randomized and 2 weeks apart. Post stress responses were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…We are not aware of any study that has studied prolonged recovery times following presyncope. Our results are also in agreement with the recent observations that recovery periods from stressors might be more relevant to the development of diseases than the actual stress itself (for details see [29][30]). …”
Section: Discussionsupporting
confidence: 93%
“…We are not aware of any study that has studied prolonged recovery times following presyncope. Our results are also in agreement with the recent observations that recovery periods from stressors might be more relevant to the development of diseases than the actual stress itself (for details see [29][30]). …”
Section: Discussionsupporting
confidence: 93%
“…To sum up, this holistic analysis showed that MAP is the most salient variable to predict failure to complete the experiment. This is in agreement with the observation that blood pressure is a primarily related variable during stress application, as was reported first by Julius (Julius 1991) and confirmed in subsequent studies (Goswami et al 2010, 2011, 2012; Patel et al 2016). …”
Section: Discussionsupporting
confidence: 91%
“…All variables were computed across the 3-min epochs of picture presentation and for 3-min epochs preceding each of the three picture conditions (baselines), in order to control for effects of initial transient responses due to the orthostatic challenge (Goswami et al, 2010; Lackner, Goswami, Papousek, et al, 2010).…”
Section: Methodsmentioning
confidence: 99%